2009
DOI: 10.1088/0741-3335/51/7/075016
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide modes in a relativistic electron beam with an axial magnetic field

Abstract: Dispersion relations (DRs) for the azimuthally symmetric waves in a cylindrical metallic waveguide completely filled with a magnetized relativistic electron beam are investigated within the framework of cold-fluid description. The defocusing effect of self-fields is counteracted by considering a rotating electron beam. Both electrostatic and electromagnetic waves are investigated by a general electromagnetic analysis. As an approximation, waves are separated into transverse magnetic (TM) and transverse electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The stability of rotating relativistic electron beam in a uniform magnetic field was studied by Han [20]. Dispersion relations for the azimuthally symmetric waves in a cylindrical metallic waveguide completely filled with a rotating magnetized relativistic electron beam were investigated within the framework of cold-fluid description [21]. Rouhani et al [22] found high-frequency eigenmodes of a cylindrical metallic waveguide partially filled with a relativistic electron beam guiding by the ion channel.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of rotating relativistic electron beam in a uniform magnetic field was studied by Han [20]. Dispersion relations for the azimuthally symmetric waves in a cylindrical metallic waveguide completely filled with a rotating magnetized relativistic electron beam were investigated within the framework of cold-fluid description [21]. Rouhani et al [22] found high-frequency eigenmodes of a cylindrical metallic waveguide partially filled with a relativistic electron beam guiding by the ion channel.…”
Section: Introductionmentioning
confidence: 99%